Fake news: Susceptibility, awareness, and solutions - Tiziana Assenza; Alberto Cardaci; Stefanie J. Huber (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2024)
The proliferation of fake news poses a growing global threat, affecting politics, individual decision-making, and economic outcomes. This column discusses how informing individuals about their susceptibility to fake news affects their willingness to pay to protect themselves from misinformation. While people often overestimate their ability to discern fake news, raising awareness about their susceptibility affects - causally and positively - their willingness to pay to protect themselves from the adverse consequences of fake news, such as by investing in fact-checking services.
Keywords: 330; Fake news; Misinformation